The impact of livestock asset transfers on the livelihoods of the ultra-poor - Das, Narayan; Kamruzzaman, Md.; Ahmed, Md. Shakil (Taylor and Francis, 2024)
This article was published in The Development in Practice [©2022 Rights managed by Taylor & Francis ] and the definite version is available at: https://doi.org/10.1080/09614524.2022.2037518 The Article's website is at: https://www.tandfonline.com/doi/full/10.1080/09614524.2022.2037518